Artistic and stylistic features of the tale of "Cupid and Psyche" (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
In the article the question of the existence of stylistic features tales that are typical signs of folk magic, fantastic tales, but also contribute to the realization of the image of the people's worldview, makes the tale more fantastic. Also thanks to the artistic and stylistic features in the tale of "Cupid and Psyche" traced the intertwining of fantasy and reality, originality, reflection of life, human characters, which is the idea of nationality.
Keywords: fairy tale; fantasy, magic; reality; story; artistic and stylistic features